Mesoporous MgTa2O6 thin films with enhanced photocatalytic activity: On the interplay between crystallinity and mesostructure - Wu, Jin-Ming; Djerdj, Igor; Graberg, Till von; Smarsly, Bernd M. (Beilstein Journal of Nanotechnology, 2012)
Ordered mesoporous, crystalline MgTa2O6 thin films with a mesoscopic nanoarchitecture were synthesized by evaporation-induced self-assembly (EISA) in combination with a sol–gel procedure. Utilization of novel templates, namely the block copolymers KLE (poly(ethylene-co-butylene)-b-poly(ethylene oxide)) and PIB6000 (CH3C(CH3)2(CH2C(CH3)2)107CH2C(CH3)2C6H4O(CH2CH2O)100H), was the key to achieving a stable ordered mesoporous structure even upon crystallization of MgTa2O6 within the mesopore walls. The effect of the calcination temperature on the ability of the mesoporous films to assist the photodegradation of rhodamine B in water was studied. As a result, two maxima in the photocatalytic activity were identified in the calcination temperature range of 550–850 °C, peaking at 700 °C and 790 °C, and the origin of this was investigated by using temperature-dependent X-ray scattering. Optimal activity was obtained when the mesoporous film was heated to 790 °C; at this temperature, crystallinity was significantly high, with MgTa2O6 nanocrystals of 1.6 nm in size (averaged over all reflections), and an ordered mesoporous structure was maintained. When considering the turnover frequency of such photocatalysts, the optimized activity of the present nanoarchitectured MgTa2O6 thin film was ca. four times that of analogous anatase TiO2 films with ordered mesopores. Our study demonstrated that high crystallinity and well-developed mesoporosity have to be achieved in order to optimize the physicochemical performance of mesoporous metal-oxide films.
Keywords: magnesium tantalate; mesoporous materials; photocatalytic activity; self-assembly; thin films

(untitled) - Ferrari, C. R.; Hernandes, A. C. (J. Eur. Ceram. Soc., 2002)

(untitled) - Tealdi, C.; Islam, M. S.; Malavasi, L.; Flor, G. (J. Solid State Chem., 2004)

(untitled) - Huang, C.-L.; Chiang, K.-H.; Huang, C.-Y. (Mater. Chem. Phys., 2005)

(untitled) - Kim, E. S.; Kim, S. J.; Lee, H. G. (J. Ceram. Soc. Jpn., 2008)

(untitled) - Sun, D. C.; Senz, S.; Hesse, D. (J. Eur. Ceram. Soc., 2004)

(untitled) - Navale, S. C.; Samuel, V.; Ravi, V. (Mater. Lett., 2005)

(untitled) - Navale, S. C.; Ravi, V. (Mater. Sci. Eng., B, 2005)

(untitled) - Mergen, A. (Ceram. Int., 2009)

(untitled) - Ganguli, A. K.; Nangia, S.; Thirumal, M.; Gai, P. L. (J. Chem. Sci., 2006)

(untitled) - Kato, H.; Kudo, A. (Chem. Phys. Lett., 1998)

(untitled) - Kondo, J. N.; Uchida, M.; Nakajima, K.; Daling, L.; Hara, M.; Domen, K. (Chem. Mater., 2004)

(untitled) - Smarsly, B.; Grosso, D.; Brezesinski, T.; Pinna, N.; Boissière, C.; Antonietti, M.; Sanchez, C. (Chem. Mater., 2004)

(untitled) - Grosso, D.; Boissière, C.; Smarsly, B.; Brezesinski, T.; Pinna, N.; Albouy, P. A.; Amenitsch, H.; Antonietti, M.; Sanchez, C. (Nat. Mater., 2004)

(untitled) - Wang, Y.; Brezesinski, T.; Antonietti, M.; Smarsly, B. (ACS Nano, 2009)

(untitled) - Beyers, E.; Cool, P.; Vansant, E. F. (J. Phys. Chem. B, 2005)

(untitled) - Sakatani, Y.; Grosso, D.; Nicole, L.; Boissiere, C.; Soler-Illia, G. J. de A. A.; Sanchez, C. (J. Mater. Chem., 2006)

(untitled) - Groenewolt, M.; Brezesinski, T.; Schlaad, H.; Antonietti, M.; Groh, P. W.; Iván, B. (Adv. Mater., 2005)

(untitled) - Smarsly, B.; Antonietti, M. (Eur. J. Inorg. Chem., 2006)

(untitled) - Brezesinski, T.; Smarsly, B.; Iimura, K.-i; Grosso, D.; Boissiere, C.; Amenitsch, H.; Antonietti, M.; Sanchez, C. (Small, 2005)

(untitled) - Ruland, W.; Smarsly, B. M. (J. Appl. Crystallogr., 2007)

(untitled) - Wu, J.-M.; Antonietti, M.; Gross, S.; Bauer, M.; Smarsly, B. M. (ChemPhysChem, 2008)

(untitled) - Zhang, L.; Yu, J. C. (Chem. Commun., 2003)

(untitled) - Wu, J.-M.; Qi, B. (J. Am. Ceram. Soc., 2008)

(untitled) - Wu, J.-M.; Zhang, T.-W.; Zeng, Y.-W.; Hayakawa, S.; Tsuru, K.; Osaka, A. (Langmuir, 2005)

(untitled) - Alvaro, M.; Aprile, C.; Benitez, M.; Carbonell, E.; Garcia, H. (J. Phys. Chem. B, 2006)

(untitled) - Linsebigler, A. L.; Lu, G.; Yates, J. T. (Chem. Rev., 1995)

(untitled) - Carp, O.; Huisman, C. L.; Reller, A. (Prog. Solid State Chem., 2004)

(untitled) - Wu, J.-M.; Huang, B.; Zeng, Y.-H. (Thin Solid Films, 2006)

(untitled) - Brezesinski, T.; Groenewolt, M.; Antonietti, M.; Smarsly, B. (Angew. Chem., Int. Ed., 2006)

(untitled) - Zhao, J.; Sallard, S.; Smarsly, B. M.; Gross, S.; Bertino, M.; Boissière, C.; Chen, H.; Shi, J. (J. Mater. Chem., 2010)